FALSE POSITIVITY OF SEROLOGICAL TESTS FOR HEPATITIS C VIRUS - Ali, Anwar; Lal, Amreek (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hepatitis C virus infection is now one the common infection in Pakistan. Patients are routinely screened by antibody assays. Objective of this study was to assess the viremia in patients labelled as anti-HCV positive by ELISA. Methods: It this retrospective study patients labelled as anti HCV positive by ELISA were assessed for HCV RNA by polymerase chain reaction. The 254 HCV positive cases which were analysed by MEIA method on AxSYM System were selected for RNA extraction by RT-PCR upon Cepheid thermal cycler using TaqMan technology and subsequent for amplification. Results: Out of 254 anti HCV positive by ELISA, viremia was shown in 211 patients; the remaining 43 (16.92%) samples were false positive. Conclusion: Out of a total 254 anti HCV positive patients, 211 had viremia by RT-PCR. The false positivity noted was 16.9%. Keywords: Anti HCV, RT-PCR, HCV, Blood